No Tea, No Shade : New Writings in Black Queer Studies - Johnson, E. Patrick, 1967- (Book collections on Project MUSE., 2016)
The follow-up to the groundbreaking Black Queer Studies, the edited collection "No Tea, No Shade" brings together nineteen essays from the next generation of scholars, activists, and community leaders doing work on black gender and sexuality. Building on the foundations laid by the earlier volume, this collection's contributors speak new truths about the black queer experience while exemplifying the codification of black queer studies as a rigorous and important field of study. Topics include "raw" sex, pornography, the carceral state, gentrification, gender nonconformity, social media, the relationship between black feminist studies and black trans studies, the black queer experience throughout the black diaspora, and queer music, film, dance, and theater. The contributors both disprove naysayers who believed black queer studies to be a passing trend and respond to critiques of the field's early U.S. bias. Deferring to the past while pointing to the future, No Tea, No Shade pushes black queer studies in new and exciting directions.